In-situ investigation on the deformation and damage behaviour of diamond-like carbon coated thin films under uniaxial loading - Schaufler, Jens; Durst, Karsten; Massler, Orlaw; Göken, Mathias (Thin Solid Films, 2009)
In the present work, the failure behaviour of diamond-like carbon (DLC) coatings on thin steel substrate under uniaxial tensile loading is analyzed in-situ in scanning electron microscopy as well as ex-situ using focused ion beam cross section and transmission electron microscopy. Aim of the work is to find correlations between the failure behaviour of the coating system, the adhesion and the stress–strain behaviour of a DLC coating system under tensile loadings conditions. Therefore thin amorphous DLC films were coated onto thin stainless steel foils using a plasma assisted chemical vapour deposition technique. It is found from the in-situ investigations that at increasing strains cracks were formed in the coating, with decreasing spacing at higher strains. By comparing uncoated steels foils with coated systems the stress–strain behaviour of a DLC coating was determined. The DLC coating, although already strongly cracked, bears loads up to a total strain of 15%. Cross section analyses with a focused ion beam and microscopy techniques supported these investigations. During straining the formation of two deformation bands adjacent to the Cr adhesion layer was observed. This deformation bands also indicate a high interfacial adhesion.
WW1::811